PENJAMIN MUTU EXTERNAL DI LEMBAGA PENDIDIKAN - Abdillah Abdillah; Amril Mustofa; Novita Sari (Universitas Dharmawangsa, 2020)
External Quality Assurance System (SPME) or Accreditation, assessment activities to determine the feasibility of study programs and tertiary institutions. Thus, the study program accreditation is an assessment activity to determine the feasibility of a study program, while university accreditation is an assessment activity to determine the eligibility of a tertiary institution. External Quality Assurance System is a verification process by the government carried out by BAN PT on the implementation of the Internal Quality Assurance System to meet or exceed National Education Standards in the form of accreditation. Informal quality assurance is carried out by a quality circle in the organization (quality circle) internal) with the main task of determining quality standards, assessment systems, and developing instruments to carry out such assessments or audits. In determining, quality standard is the first step that must be taken in the context of formal and informal quality assurance. Formal quality assurance through ISO is an application and quality assurance principles in which determine the processes and systems that are used as guidelines by the institution.